2007
DOI: 10.1021/ja074115f
|View full text |Cite
|
Sign up to set email alerts
|

A Peptide Dendrimer Enzyme Model with a Single Catalytic Site at the Core

Abstract: Catalytic esterase peptide dendrimers with a core active site were discovered by functional screening of a 65,536-member combinatorial library of third-generation peptide dendrimers using fluorogenic 1-acyloxypyrene-3,6,8-trisulfonates as substrates. In the best catalyst, RMG3, ((AcTyrThr)(8)(DapTrpGly)(4)(DapArgSerGly)(2)DapHisSerNH2), ester hydrolysis is catalyzed by a single catalytic histidine residue at the dendrimer core. A pair of arginine residues in the first-generation branch assists substrate bindin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
58
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 76 publications
(64 citation statements)
references
References 59 publications
6
58
0
Order By: Relevance
“…Although the peptide dendrimer sequence space is much smaller than that of a real protein, the dendritic topology avoids the necessity of folding by forcing the peptide dendrimer to adopt a globular structure. The dendritic architecture results in disordered conformations resembling the molten globule state of proteins, [40][41][42] with a dynamic tertiary structure containing few native-like secondary structure elements such as a-helices and b-sheets. 43 In contrast to proteins, peptide dendrimers are entirely stable towards denaturation.…”
Section: 33mentioning
confidence: 99%
“…Although the peptide dendrimer sequence space is much smaller than that of a real protein, the dendritic topology avoids the necessity of folding by forcing the peptide dendrimer to adopt a globular structure. The dendritic architecture results in disordered conformations resembling the molten globule state of proteins, [40][41][42] with a dynamic tertiary structure containing few native-like secondary structure elements such as a-helices and b-sheets. 43 In contrast to proteins, peptide dendrimers are entirely stable towards denaturation.…”
Section: 33mentioning
confidence: 99%
“…[9,[10][11][12][13] Structurally, peptide dendrimers behave as molten globules in aqueous solution. [14] Contrary to folded proteins, however, they cannot be denatured to a linear disordered state; this suggests that they might be resistant to proteolytic degradation by blocking access of the protease to possible cleavage sites. Indeed multiple antigenic peptides, which are synthetic linear peptides attached to a dendritic polylysine core, have been reported to be resistant to proteolytic degradation.…”
Section: Introductionmentioning
confidence: 99%
“…We have shown previously with the example of esterase-active dendrimers that this type of third generation dendrimer can be hydrophobically collapsed, and that their degree of compaction is comparable to molten globule, and sometimes, fully-folded proteins; this suggests that such hydrophobically collapsed dendrimers might be resistant to proteolysis. [14] However, while these dendrimers were much less reactive than the second generation dendrimers above, quantitative proteolysis could be obtained when using 50 mg mL À1 of either trypsin or a-chymotrypsin. Specific cleavage was confirmed in the case of trypsin by identification of the fragments by MS, which showed that all arginine cleavage sites had reacted ( Table 2).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 Dendrimers are monodisperse oligomers and polymers usually with special function. [3][4][5] They are usually related to the fields of catalysis, [6][7][8][9] drug delivery, [10][11][12][13] liquid crystalline materials 14 and contrast media for clinic diagnosis. 15,16 In a few reported works, dendrimers are used in chromatography.…”
Section: Introductionmentioning
confidence: 99%